The Development and Clinical Significance of the Curve of Spee in Orthodontics and Prosthodontics - Conventional and Digital Approaches - Almutawa, Nawal (Archive of Orofacial Data Science, 2025)
AIM: To enhance the understanding of the development of the curve of Spee, its significance in orthodontics and prosthodontics, and its management using conventional and digital orthodontics. METHODS: Records were gathered from PubMed (279) and Google Scholar (421), along with four from supplementary methods. After eliminating 110 duplicates, 590 records were screened. Exclusion criteria removed studies on animals, seminar presentations, opinion pieces, and incomplete data. This process led to the inclusion of 16 articles after assessing potential relevance. RESULTS: Insights into the historical context and development of the curve of Spee were addressed. Various methods of measuring the curve of Spee, including cast models, 3D models, lateral cephalograms, and CBCT, were briefly discussed. Its significance in prosthodontics and orthodontics was thoroughly explained. Methods for leveling the curve of Spee were examined in both conventional and digital orthodontics, along with their long-term stability. CONCLUSION: Through a comprehensive review of the literature, several key findings have emerged that elucidate its historical development and role in both orthodontics and prosthodontics. Leveling the curve of Spee in orthodontics is critical, as orthodontists encounter it in nearly every case of treatment. It is recommended that further studies be conducted.